The Challenging Task of Governing Cross-Border Investment in Peripheral Regions: Polish Investors in Northeast Germany - Kinder, Sebastian; Lis, Kamil; Peiker, Wolfdietrich; Suwala, Lech (Quaestiones Geographicae, 2014)
The article investigates the challenging task of governing cross-border investment in peripheral regions. The main objective is to identify common opportunities and obstacles in the Pomerania Euroregion by taking the case study of Polish citizens/ entrepreneurs investing in northeast Germany. This relatively new phenomenon is accompanied by large uncertainties and risks, and lacks further empirical insights. At the same time it breaks new ground, creates alternatives, calls for the development of efficient modes of cross-border cooperation and addresses mutual governance issues on an inter-regional basis between manifold stakeholders on both sides of the border. The case study summarises findings from fieldwork, elaborates a quantitative and qualitative assessment of cross-border governance measures within formal and informal institutions, and tries to formulate policy recommendations for prospective approaches